Faktor-Faktor yang Berhubungan dengan Kecendrungan Turnover Perawat di Rumah Sakit Islam “Ibnu Sina” Yarsi Sumbar Bukittinggi: Factors Associated with Nurse Turnover Tendency Turnover of Nurses at the Islamic Hospital “Ibnu Sina” Yarsi Sumbar Bukittinggi - Bambang Aryanto; Reni Prima Gusty; Yulastri Arif (Fakultas Keperawatan Universitas Andalas, 2011)
High turnover is a problem in the management of human resources at hospitals. The nurse turnover rate at Islamic Hospital